Air-clad photonic lanterns: fabrication and applications. (1st May 2022) - Mathew, Neethu Mariam; Grüner-Nielsen, Lars; Lillieholm, Mads; Galili, Michael; Rottwitt, Karsten
Abstract: The fabrication steps for an air-clad photonic lantern that can excite the first two LP mode groups in a multimode fiber are presented in this paper. A multiplexing crosstalk below −16.8 dB is measured on the fabricated lantern using S 2 imaging technique over a wavelength of 1525–1575 nm. The de-multiplexing crosstalk is measured for both LP 01 and LP 11 mode groups as −16.8 dB and −9.4 dB respectively using loss measurements. 2 × 40 Gbs −1 MIMO-less mode division multiplexing (MDM) transmission through 7 m of two mode step index fiber is demonstrated using the fabricated photonic lanterns. 2 × 10 Gbs −1 MIMO-less MDM transmission through 1.6 km standard 50/125 µ m multimode fiber is also demonstrated and a Q value higher than 3.7 is obtained for both spatial channels over all input polarizations. Simple intensity modulation and direct detection schemes are used for these MDM transmissions.